Proline-rich tyrosine kinase 2 downregulates peroxisome proliferator–activated receptor gamma to promote hypoxia-induced pulmonary artery smooth muscle cell proliferation - Bijli, Kaiser M. (Pulm Circ, 2016)
Abstract. Hypoxia stimulates pulmonary hypertension (PH), in part by increasing the proliferation of human pulmonary artery smooth muscle cells (HPASMCs) via sustained activation of mitogen-activated protein kinase, extracellular signal–regulated kinases 1 and 2 (ERK 1/2), and nuclear factor-kappa B (NF-κB); elevated expression of NADPH oxidase 4 (Nox4); and downregulation of peroxisome proliferator–activated receptor gamma (PPARγ) levels. However, the upstream mediators that control these responses remain largely unknown. We hypothesized that proline-rich tyrosine kinase 2 (Pyk2) plays a critical role in the mechanism of hypoxia-induced HPASMC proliferation. To test this hypothesis, HPASMCs were exposed to normoxia or hypoxia (1% O(2)) for 72 hours. Hypoxia activated Pyk2 (detected as Tyr402 phosphorylation), and inhibition of Pyk2 with small interfering RNA (siRNA) or tyrphostin A9 attenuated hypoxia-induced HPASMC proliferation. Pyk2 inhibition attenuated ERK 1/2 activation as early as 24 hours after the onset of hypoxia, suggesting a proximal role for Pyk2 in this response. Pyk2 inhibition also attenuated hypoxia-induced NF-κB activation, reduced HPASMC PPARγ messenger RNA levels and activity, and increased NF-κB-mediated Nox4 levels. The siRNA-mediated PPARγ knockdown enhanced Pyk2 activation, whereas PPARγ overexpression reduced Pyk2 activation in HPASMCs, confirming a reciprocal relationship between Pyk2 and PPARγ. Pyk2 depletion also attenuated hypoxia-induced NF-κB p65 activation and reduced PPARγ protein levels in human pulmonary artery endothelial cells. These in vitro findings suggest that Pyk2 plays a central role in the proliferative phenotype of pulmonary vascular wall cells under hypoxic conditions. Coupled with recent reports that hypoxia-induced PH is attenuated in Pyk2 knockout mice, these findings suggest that Pyk2 may represent a novel therapeutic target in PH.